Reply to: Causal claims, causal assumptions and protected area impact - Jedediah F., Brodie; Mohd Azlan, Jayasilan; Cheng, Chen; Oliver R., Wearn; Mairin C. M., Deith; James G., C. Ball; Eleanor M., Slade; David F. R., P. Burslem; Shu, Woan Teoh; Peter J., Williams; Anh, Nguyen; Jonathan H., Moore; et al. (Springer Nature, 2025)
In the accompanying Comment, Geldmann et al.1 incorrectly claim that protected area (PA) efficacy cannot be established without biodiversity data that predates establishment of the PA. Spatial correlates of diversity are known as a result of centuries of ecological research; our analyses controlled for these factors in a variety of ways in order to isolate the impacts of protection per se on bird and mammal biodiversity. The proposition of Geldmann et al. that our results are biased because PAs were established in areas with high natural biodiversity ignores these analytical controls, is naive to the realities of on-the-ground conservation, and has been disproved by recent research. Although we look forward to future work that improves on our predictions, our study provides robust estimates of the biodiversity impacts of PAs across hyperdiverse Southeast Asia2—information that is critically needed to support large-scale conservation objectives.